Analysis of the Causes of Production Process Failure with the FishBone Diagram Method and Implementation of TQM to Improve Product Quality in the Manufacturing Industry of PT Emsonic Indonesia - Aqilah, Jeanytha Thifal; Amelia, Risma; Prasetyo , Eko; Boimau, Devrin; Fadli, Rozul; Prastyo, Yudi (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Emsonic Indonesia is a company engaged in plastic mold manufacturing, which produces speakers in the form of units, case assemblies, and finished forms based on RPP (Product Delivery Plan). PT. Emsonic Indonesia strives to provide the best for customers, by improving product quality. This study aims to analyze the causes of product defects, use the Fish Bone diagram method to analyze the causes, and apply Total Quality Management (TQM) to improve product quality at PT. Emsonic Indonesia. Based on the results of the fish bone diagram method, it can be seen that product defects come from human, mechanical, method, management, material, and environmental factors. In the human factor, it was found that employees did not receive adequate training regarding the operation of machines and correct work procedures giving rise to NG products because they exceeded the limits of inspection standards. Meanwhile, based on Total Quality Management (TQM), it was able to explain the improvement of product quality by 51.3% while the remaining 48.7% was explained by other factors that were not studied in this study. Meanwhile, the results of the F test show that simultaneously the variables of the production process and Total Quality Management (TQM) simultaneously have a positive and significant effect on the improvement of product quality and the results of the t test show that the variables of the production process and Total Quality Management (TQM) have a positive and significant effect on the improvement of product quality at PT. Emsonic Indonesia.